Early initiation of renal replacement therapy improves survival in patients with acute kidney injury - Knežević Violeta; Azaševac Tijana; Šibalić-Simin Marija; Sladojević Vesna; Urošević Ivana; Ćelić Dejan (Vojnosanitetski Pregled)
Background/Aim. Defining renal replacement therapy (RRT) initiation in critically ill patients with acute kidney injury (AKI) has become an imperative for nephrologists and intensivists. The aim of this study was to determine 28-day survival and the renal function recovery in patients with AKI. Methods. A single-center retrospective study included 385 surgical and non-surgical patients with AKI and episode of AKI in chronic kidney disease who were admitted to the Emergency Center of Clinical Center of Vojvodina (Novi Sad, Serbia) between 2014 and 2017 and received RRT. Patients with the Kidney Disease Improving Global Outcomes (KDIGO) stage 2 AKI and/or volume overload were assigned to the “early” group with RRT (dialysis) start within 24 h of the diagnosis; patients with poor response to conservative treatment or evidence of clinical complications associated with AKI were assigned to the “late” RRT group. Results. Based on the retrospective analysis we found that 241 patients (62.6%) received “early” RRT within 24 h. Patients in the “early” RRT group had significantly higher survival compared to the “late” RRT group (63.9% vs. 36.1%; p = 0.001). The “early” RRT group had more patients with renal function recovery (56.8%), but without statistical significance (p = 0.514). The patients who started RRT within 24 hours with the Sequential Organ Failure Assessment (SOFA) score of 1–3 were twice likely to recover renal function in relation to the patients with the SOFA score of 4 or higher [odds ratio (OR) = 2.01; 95% confidence interval (CI): 1.37–2.95; p < 0.001], while septic patients had a 62% lower chance of renal function recovery in relation to non-septic patients (OR = 0.38; 95% CI: 0.18–0.82; p = 0.013). In the “late” RRT group, it was found that non-diabetic patients had 3.8 times greater chance for renal function recovery compared to diabetic patients (OR = 3.53; 95% CI: 1.27–9.83; p = 0.016). Conclusions. Patients with the early initiation of RRT had significantly improved 28-day survival.